The Effect of Technology Utilization on Operations Performance with Process Innovation as a Mediator - Bebasari, Nataliana; Maryadi, Adi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate the effect of technology utilization on operating performance, considering process innovation as a mediator in an organizational context, using the Smart Partial Least Squares (Smart PLS) analysis tool. The study involved 72 respondents from various industries and business sectors in Indonesia. The results showed that technology utilization has a positive and insignificant effect on operating performance. In addition, process innovation proved to be a strong mediator in the relationship between technology utilization and operating performance. This indicates that organizations that are able to utilize technology effectively are more likely to improve their operating performance, especially if they can generate innovation in their business processes. This research provides a deeper understanding of how technology can be a catalyst in improving an organization's operating performance, especially when supported by strong process innovation efforts. These results have important implications for organizations in their efforts to compete effectively in the ever-changing digital age. This research also contributes to the theoretical understanding of the relationship between technology utilization, process innovation, and operating performance in a business context. The practical implication of this study is that organizations should consider technology utilization and process innovation as an integral part of their strategy to improve operating performance